(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A key for larval instars discrimination of the pea aphid, Acyrthosiphon pisum (Harris) is here presented. The key is based on characters that are easily detectable in living aphids, feeding on their usual substratum. First and second instar have 5-segmented antennae, but the second instar shows a dark band at the 3rd antennal segment. Third and fourth instars have 6-segmented antennae, and discrimination is based upon the different shape of cauda. Moulting occurrence between one instar and the next one is verified tagging the aphid dorsum with pens for overhead projection.